Demographic changes and pension reform in the Republic of Korea - Hyungpyo Moon (Asian Development Bank Institute (ADBI), 2009)
This paper conducted a quantitative assessment based on a simulation analysis of what impact the reformed Korean National Pension Act on July 2007 could bring on its sustainability, equity, and adequacy, and then it inquires into policy implications for further evelopment of the system. Overall, the recent reform is regarded as positive in the sense hat efforts to prepare preemptive measures were made concerning the coming era of population aging by the way of financial stabilization, consolidation of pensionable right, and system rationalization. But, at the same time, challenges that require additional security from efficiency and equity perspectives still remain. In this regard, this paper suggests future policy agendas for resolution as follows: First, setting up a clear target for financial stabilization, and gradual increase of contribution rate; Second, curbing pressure from increasing contribution rate through improvement on pension fund management system and its profitability; and third, emphasizing the urgent need to raise the current earnings ceiling and to establish a multi-pillar old age income security system by activating corporate retirement pensions, private pensions, and reverse mortgages.
Keywords: H55; 330; Alternde Bevölkerung; Rentenreform; Südkorea